2023
DOI: 10.3390/buildings13081994
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Studies on Heat Transfer in Buildings with Radiant Cooling Systems

Abstract: Due to their benefits in interior thermal comfort, energy saving, and noise reduction, radiant cooling systems have received wide attention. Radiant cooling systems can be viewed as a part of buildings’ maintenance structure and a component of cooling systems, depending on their construction. This article reviews studies on heat exchange in rooms utilizing radiant cooling systems, including research on conduction in radiant system structures, system cooling loads, cooling capacity, heat transfer coefficients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…This operation is generally in a non-steady state, and depends on many parameters [23,24]. As previous research has indicated, parameters like pipe diameter, material, pipe depth and spacing, supply water temperature, and flow rate influence the cooling capacity of radiant cooling systems [21]. For radiant systems in use, the cooling capacity can be adjusted by changing the water temperature or water flow rate, ultimately influencing the cooling surface temperature.…”
Section: Space Cooling Load and Control Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…This operation is generally in a non-steady state, and depends on many parameters [23,24]. As previous research has indicated, parameters like pipe diameter, material, pipe depth and spacing, supply water temperature, and flow rate influence the cooling capacity of radiant cooling systems [21]. For radiant systems in use, the cooling capacity can be adjusted by changing the water temperature or water flow rate, ultimately influencing the cooling surface temperature.…”
Section: Space Cooling Load and Control Variablesmentioning
confidence: 99%
“…With regard to the combined system discussed in this study, several parameters can be adjusted to meet cooling demand, such as the supply air temperature of the ventilation systems, the supply water temperature of cooling floors, etc. Different control strategies may lead to different levels of energy use, even while maintaining the same comfort level, as radiant floors primarily exchange heat through radiation, while air ventilation systems exchange heat by convection [21]. However, there has been limited research performed on indoor environments in large spaces with regard to radiant floor/displacement ventilation system combinations under different weather conditions and different control strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, many studies have been conducted on the optimization of their energy efficiency [5][6][7][8]. It has been shown that radiant cooling systems are able to significantly reduce energy consumption compared with conventional convective air conditioning systems [9][10][11].…”
Section: Introductionmentioning
confidence: 99%